Spectrophotometric Determination of Ascorbic acid in Aqueous Solutions and in Pharmaceuticals formulations - Hussein, Ahmed Z Mohamed (Al-Nahrain Journal of Science, 2013)
A new sensitive colorimetric method for determination of ascorbic acid tablet in aqueous solution. The method is based on the formation of colored azo dye by diazotization of 2, 4-dichloroaniline followed by azo-coupling reaction between the resulting product and ascorbic acid. The optimum conditions that gave maximum absorption of azo dye at535nm, with best concentration of reactant and order of addition were studied to get the highest sensitivity (ε=2315) L.mol-1.cm-1 with a wide range of calibration curves (2-70) µg/ml good repeatability (RSD% 0.68 and 1.49), the recovery (99.56 - 100.30)%, Erel% (-0.20 and 0.44) were gave , Pharmaceutically prepared tablets were measured with the new technique using standard addition method given a very good recovery % (101.25 and 98.77) with a small Erel% (-1.25 and 1.23).